Organizational resources, organizational engagement climate, and employee engagement. Issue 1 (6th February 2018) - Albrecht, Simon; Breidahl, Emil; Marty, Andrew
Abstract : Purpose: The majority of job demands-resources (JD-R) research has focused on identifying the job demands, job resources, and personal resources that influence engagement. The purpose of this paper is to assess the significance of proposed associations between organizationally focused resources, organizational engagement climate, and engagement. Design/methodology/approach: The authors tested a model proposing that six specific organizational resources would have positive associations with organizational engagement climate, and positive direct and indirect associations with job resources and employee engagement. Confirmatory factor analysis (CFA) and structural equation modeling (SEM) were conducted on cross-sectional survey data provided by 1, 578 employees working in a range of different organizations. Findings: The CFA and SEM analyses yielded good fit to the data. As proposed, all six organizational resources were positively associated with organizational engagement climate. Four were positively associated with job resources, and two were positively associated with engagement. Organizational engagement climate was positively associated with job resources and employee engagement. Significant indirect relationships were also observed. Research limitations/implications: Despite self-reported data and a cross-sectional design, tests of common method variance did not suggest substantive method effects. Overall, the results contribute new insights about what may influence engagement, and highlight the importance of organizational engagement climate as a motivational construct. Practical implications: The research offers up potentially useful measures of six organizational resources and a measure of organizational engagement climate that can complement and broaden the current focus on job-level diagnostics. As such, targeted management action and survey feedback processes can be used to identify processes to build sustainable organizational engagement capability. Originality/value: No previous research has identified a comprehensive set of organizational resources, operationalized organizational engagement climate, or examined their relationships within a JD-R context. The results suggest that the JD-R can perhaps usefully be extended to include more organizationally focused constructs.